Preservation of the integrity of facial nerve in vestibular schwannoma microsurgery: A consecutive study of 127 clinical cases focusing on nervus intermedius - Li, Yue; Peng, Hao; Zhang, Sen; Long, Wenyong; Pan, Yimin; Li, Yang; Wu, Changwu; Xiao, Kai; Wang, Xiangyu; Su, Jun; Qin, Chaoying; Liu, Qing (Frontiers in Oncology, 2023)
Background Nervus intermedius (NI) injuries are not given enough attention by neurosurgeons during vestibular schwannoma (VS) surgery. Preservation of NI function is essential for the integrity and continuity of the facial nerve, although this can be challenging. We identified the risk factors for NI injury and proposed our experience for optimizing NI preservation based on our cases. Methods We retrospectively analyzed clinical data from a consecutive series of 127 patients with VS who underwent microsurgery via the retrosigmoid approach from 2017 to 2021 at our institution. The baseline characteristics of the patients were collected from the medical records, and the incidence of NI dysfunction symptoms was obtained by outpatient and online video follow-up 6 months after surgery. The surgical procedures and techniques used were described in detail. The data were analyzed in relation to sex, age, tumor location (left or right), Koos grading scale, internal acoustic canal (IAC) invasion (TFIAC Classification), brainstem adhesion, tumor characteristics (cystic or solid), tumor necrosis, and preoperative House–Brackmann (HB) grading by univariate and multivariate analyses. Results Gross tumor removal was achieved in 126 (99.21%) patients. Subtotal removal was performed on one patient (0.79%). Twenty-three of our cases exhibited facial nerve palsy preoperatively; 21 patients had HB grade II facial palsy, and two had HB grade III. Two months after surgery, 97 (76.38%) patients had normal function of the motor portion of the facial nerve; 25 (19.69%) patients had HB Grade II facial palsy, five had Grade III (3.94%), and zero (0%) had Grade IV. Postoperatively, 15 patients experienced newly gained dry eyes (11.81%), whereas 21 cases of lacrimal disturbances (16.54%), nine of taste disturbances (7.09%), seven of xerostomia (5.51%), five of nasal hypersecretions (3.94%), and seven of hypersalivation (5.51%) were identified in our cases. Univariate and multivariate analyses revealed that the Koos grading scale and tumor characteristics (solid or cystic) were correlated with NI injury (p <0.01). Conclusion The data in this study demonstrate that although the motor function of the facial nerve is well preserved, NI disturbance is still common after VS surgery. Maintaining the integrity and continuity of the facial nerve is key to NI function. Performing bidirectional and subperineurium dissection based on even and adequate debulking is beneficial for NI preservation in VS surgery. Higher Koos grading and cystic characteristics of VS are associated with postoperative NI injuries. These two parameters can be used to guide the delineation of surgical strategy and predict the prognosis of NI function preservation.